Recombinant GM-CSF for diseases of GM-CSF insufficiency: Correcting dysfunctional mononuclear phagocyte disorders - Lazarus, Hillard M.; Pitts, Katherine; Wang, Tisha; Lee, Elinor; Buchbinder, Elizabeth; Dougan, Michael; Armstrong, David G.; Paine, Robert; Ragsdale, Carolyn E.; Boyd, Timothy; Rock, Edwin P.; Gale, Robert Peter (Frontiers in Immunology, 2023)
Endogenous granulocyte-macrophage colony-stimulating factor (GM-CSF) was identified based on its ability to support differentiation of hematopoietic stem and progenitor cells into several types of myeloid cells. GM-CSF is also now known to support maturation and maintenance of metabolic capacity in mononuclear phagocytes, including monocytes, macrophages, and dendritic cells. Mononuclear phagocytes sense and attack potential pathogens, present antigens to adaptive immune cells, and recruit other immune cells. Additionally, recombinant human (rhu) GM-CSF (e.g., sargramostim [glycosylated, yeast-derived rhu GM-CSF]) has immune modulating properties and can restore normal function of mononuclear phagocytes rendered dysfunctional by deficient or insufficient endogenous GM-CSF. Mononuclear phagocytes include circulating monocytes, tissue bound macrophages, and dendritic cells that might be either circulating or tissue bound. Correcting GM-CSF insufficiency by giving exogenous rhu GM-CSF (e.g., sargramostim) in investigative fashion may control or treat diseases caused by mononuclear phagocyte dysfunction. Recent data indicate positive GM-CSF effects on mitochondrial function and cell metabolism, augmentation of phagocytosis and efferocytosis, and immune cell modulation. We discuss emerging data on GM-CSF biology and rhu GM-CSF activity in diverse disorders caused or exacerbated by GM-CSF deficiency or insufficiency. These disorders include autoimmune pulmonary alveolar proteinosis, diverse infections (including COVID-19), and wound healing. Finally, in cancer immune checkpoint inhibitor immunotherapy, rhu GM-CSF may augment anti-cancer treatment, as well as ameliorate immune-related adverse events. We identify research gaps, opportunities, and the idea that rhu GM-CSF’s support of metabolic capacity enables diverse mononuclear phagocyte functions. In summary, rhu GM-CSF (e.g., sargramostim) might ameliorate multiple diseases of GM-CSF deficiency or insufficiency that share high unmet medical need.